IMPLEMENTASI PERATURAN DAERAH KABUPATEN SIAK NOMOR 11 TAHUN 2006 TENTANG PEMBENTUKAN BADAN USAHA MILIK DAERAH (BUMD) PT. PERMODALAN SIAK DALAM PEMBERDAYAAN EKONOMI MASYARAKAT DI KABUPATEN SIAK TAHUN 2007-2012 - Umair, Mukholis; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research aims to describe the implementation of Siak RegencyRegulation No. 11 Year 2006 on the Establishment of provincial enterprises(enterprises) PT. In the capital Siak Economic Empowerment In Siak seen in theimplementation. The usefulness of this study are as material information regardingthe implementation of the People's Empowerment held by PT. Siak starting capital togrow, develop and nurture, so as to provide input to the PT. Siak capital andprovincial governments to the realization of equitable empowerment of the people.This study uses the theory proposed by (Riant Nugroho, 2006: 158) theimplementation of the policy in principle is a way in order to achieve a policy goal,nothing more and nothing less. To implement public policy, then there are twooptions available measures that directly mengeimplementasikan in the form ofprograms or policies regulai derivative or derivative of such public policy. Themethod used in this study is qualitative methods of data that can not be expressed interms of numbers but in the form of an explanation that describes the shape of thestate, a process, a particular event. Data collection techniques using interviewtechniques and documentation of the results of this study can be concluded that theimplementation of the Regional Regulation No. 11 of 2006 is not running optimally. Itcan be seen from this type of loan can not reach the poor, not the course of 11 typesof loans that are provided and the misappropriation of funds by customers.Key Word : Implementation, PT. Permodalan Siak, Economic Empowerment.